Anti-semitism and Xenophobia*. Issue 4 (December 2017) - Kogan, Ilany
Abstract This paper explores the link between anti-Semitism and xenophobia from a psychoanalytic prism. The author claims that anti-Semitism is a particular form of xenophobia directed against Jews, with some unique characteristics. She first introduces some basic notions about xenophobia, and then discusses the origins of anti-Semitism as they are viewed in early psychoanalytic thinking and in contemporary psychoanalysis. The article explores the nature of anti-Semitism in society today, and presents some reflections on the interplay between anti-Semitism and other kinds of xenophobia.